MANAJEMEN PROGRAM TAHFIDZ AL-QUR’AN DALAM MENINGKATKAN MOTIVASI BELAJAR Al-QUR’AN SISWA DI PONDOK PESANTREN AL-HIKMAH BANDAR LAMPUNG - Anisah Vidiawati; Abdurrahman Abdurrahman; Muhammad Kharis Fadillah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the management of the Qur'an memorization program in increasing motivation to learn the Qur'an at the Al-Hikmah Islamic Boarding School in Bandar Lampung by examining the functions of planning, organizing, implementing, as well as assessing and evaluating the program. This study uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation with participants, program coordinators, memorization teachers, musyrifs, and students. Data analysis was carried out interactively through reduction, presentation, and drawing conclusions, and its validity was tested by triangulation. The results of the study indicate that the management of the tahfidz program is implemented in a structured manner through setting memorization targets, dividing mentoring tasks, implementing scheduled deposits and muroja'ah, intensive tahsin, and periodic evaluations. The implementation of these management functions provides a positive contribution in increasing students' discipline, perseverance, and motivation to learn the Qur'an. The uniqueness of this study lies in placing the management of the tahfidz program as the main variable in increasing learning motivation and revealing typical practices in the form of a fluency policy before memorization, multi-party coordination, and the habituation of One Day One Juz.